Carcinoma ex pleomorphic adenoma. Issue 10 (October 2018) - Westwood, Alice C.; Chengot, Preetha
Abstract: Carcinoma ex pleomorphic adenoma is an epithelial malignant neoplasm arising from a primary or recurrent pleomorphic adenoma and is a diagnostic challenge for cytopathologists. Diagnosis requires that elements from the benign pleomorphic adenoma and the malignant component need to be seen. We report a case of carcinoma ex pleomorphic adenoma in a patient presenting with left facial nerve palsy and a painless left parotid lump. Ultrasound imaging revealed a suspicious parotid mass and FNA cytology showed background benign myoepithelial and ductal cells, chondro-myxoid stroma, and overtly malignant epithelial and myoepithelial cells; features consistent with carcinoma ex pleomorphic adenoma. A radical parotidectomy was performed and histology confirmed the diagnosis of invasive salivary duct carcinoma ex pleomorphic adenoma. Early diagnosis of carcinoma ex pleomorphic adenoma is important and cytology plays a key role; however, findings should be correlated with radiology and clinical history and the potential limitations of cytology should be appreciated.